Light at the end of the channel: optical manipulation of intrinsic neuronal excitability with chemical photoswitches - Mourot, Alexandre; Tochitsky, Ivan; Kramer, Richard H. (Frontiers in Molecular Neuroscience, 2013)
Ion channels are transmembrane proteins that control the movement of ions across the cell membrane. They are the molecular machines that make neurons excitable by enabling the initiation and propagation of action potentials. Rapid signaling within and between neurons requires complex molecular processes that couple the sensing of membrane voltage or neurotransmitter release to the fast opening and closing of the ion channel gate. Dysfunction of an ion channel’s sensing or gating module can have disastrous pathological consequences. However, linking molecular changes to the modulation of neural circuits and ultimately to a physiological or pathological state is not a straightforward task. It requires precise and sophisticated methods of controlling the function of ion channels in their native environment. To address this issue we have developed new photochemical tools that enable the remote control of neuronal ion channels with light. Due to its optical nature, our approach permits the manipulation of the nervous system with high spatial, temporal and molecular precision that will help us understand the link between ion channel function and physiology. In addition, this strategy may also be used in the clinic for the direct treatment of some neuronal disorders.